The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1152/ajpgi.1994.267.3.g393
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin in human gallbladder bile: cholesterol pronucleating and/or mucin "link" protein?

Abstract: Some biliary proteins (pronucleators) seem to be essential factors for cholesterol crystal formation and crystal growth in bile. A recent study suggests that fibronectin is such a pronucleator in bile. Fibronectin also seems to closely interact with intestinal mucin. Since biliary mucin plays an important role in gallstone formation, such an interaction in bile may be of relevance in cholesterol gallstone formation. To more clearly elucidate the role of fibronectin in cholesterol gallstone disease, we measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
2
3
0
Order By: Relevance
“…The concentration of FN used to opsonize M. avium subsp. paratuberculosis in this investigation (2 g/ml) is equivalent to those reported for human bile (2 to 26 g/ml) (21,40). Hence, we believe that the use of FN-opsonized organisms in this investigation more closely resembles the situation in natural infections.…”
Section: Effect Of Fn On Invasion Of M Cellssupporting
confidence: 75%
“…The concentration of FN used to opsonize M. avium subsp. paratuberculosis in this investigation (2 g/ml) is equivalent to those reported for human bile (2 to 26 g/ml) (21,40). Hence, we believe that the use of FN-opsonized organisms in this investigation more closely resembles the situation in natural infections.…”
Section: Effect Of Fn On Invasion Of M Cellssupporting
confidence: 75%
“…Our results show that the soluble glycoprotein mass recovered from the Con A column was 33 Ϯ 15% of total biliary proteins comparable to the modified method (36%) of Harvey, Upadhya, and Strasberg (27). In the literature, final concentrations of added Con A-binding glycoproteins ranged from 0.25 to 2 mg/mL (19,20,27). We added a final protein concentration of 1 mg/mL, which was similar to the pathophysiological levels in the gallbladder biles used in this study.…”
Section: Soluble Con A-binding Biliary Glycoproteins Do Not Influence Detection Times Of Ch Solid and Liquid Crystalssupporting
confidence: 65%
“…Abei et al (17) reported that ␣1-acid glycoprotein accounted for up to 30% of total accelerating activity in terms of ChM crystal detection times, however, De Bruijn and colleagues (19) could not find any pro-nucleating/ crystallizing activity with ␣1-acid glycoprotein. Chijiiwa et al (14) proposed that fibronectin, also a Con A-binding protein, was a pro-nucleating/crystallizing factor; whereas, two other groups (20,21) obtained results inconsistent with any nucleation/crystallization activity of fibronectin on ChM crystal detection times. In the extensive literature (summarized in ref.…”
Section: Soluble Con A-binding Biliary Glycoproteins Do Not Influence Detection Times Of Ch Solid and Liquid Crystalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides cholesterol supersaturation [4] and gallbladder hypomotility [2,5] , kinetic protein factors that promote or inhibit cholesterol crystallization have been suggested to play key roles in cholesterol gallstone pathogenesis [6,7] . During the past decade, model bile studies indicated that several promoter or inhibitor proteins influence cholesterol crystallization in vitro [8][9][10][11][12][13][14] . Immunoglobulins were also identified as nucleating proteins in the gallbladder bile of patients with cholesterol gallstones [15,16] .…”
Section: Introductionmentioning
confidence: 99%